1999
DOI: 10.2331/fishsci.65.563
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogeny of Asian Freshwater and Marine Stingrays Based on the DNA Nucleotide and Deduced Amino Acid Sequences of the Cytochrome <i>b</i> Gene

Abstract: To elucidate the phylogenetic relationship among stingrays of three freshwater and five marine spe cies of the genera Himantura, Dasyatis, and Pastinachus, belonging to the family Dasyatidae distribut ed in Thailand, Laos, India, and Japan, we determined the nucleotide sequences of the mitochondrial DNA region encoding cytochrome b. Using two rayfish species belonging to the superfamily Mylio batoidea as out-groups, we found three clades for the collected stingrays in the family Dasyatidae from anlayses using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 6 publications
0
35
0
Order By: Relevance
“…For example, shifts from marine to FW have occurred multiple times in fish (Sezaki et al. ; Lovejoy and Collette ; Yamanoue et al. ; Bloom et al.…”
Section: Metabolic Ratementioning
confidence: 99%
“…For example, shifts from marine to FW have occurred multiple times in fish (Sezaki et al. ; Lovejoy and Collette ; Yamanoue et al. ; Bloom et al.…”
Section: Metabolic Ratementioning
confidence: 99%
“…Obligate Freshwater elasmobranchs are dominated (30 species) by myliobatoid stingrays, of which twothirds (22 species) are potamotrygonid river stingrays, Glantz & Feingold, 1990;Smith et al, 1991 By-catch Direct removal; reduction of prey base; changes in aquatic community composition & structure Miller et al, 1990;Nichols et al, 1990;Murray et al, 1992;Perra, 1992 Illegal trade in aquarium/ornamental ¢sh Direct removal; use of toxins (sodium cyanide) to collect ¢sh; decline of native ¢sh diversity Conroy et al, 1981;Derr, 1992 Introduced species Introduced predators, competition, hybridization, introduced parasites & disease, ballast water introduction Population reduction or extermination of native ¢sh, loss of prey base Taylor et al, 1984;Helfman et al, 1997 endemic to Atlantic drainages of South America. Sezaki et al (1999) found that DNA nucleotide and amino acid sequences in Indian and Thai populations of the Obligate Freshwater stingray Himantura chaophraya were clearly di¡erent, suggesting that signi¢cant evolutionary divergence occurred since their ecological isolation in di¡erent river systems. Such isolation may account for the relatively high diversity and incidence of endemism among Obligate Freshwater elasmobranchs.…”
Section: Biology Of Freshwater and Euryhaline Elasmobranchsmentioning
confidence: 99%
“…Molecular phylogeny suggests that freshwater stingrays from Southeast Asia, including H. signifer , have only marine species as their nearest relative, and they underwent multiple colonizations rather than speciations within freshwater [46]. Since the invasion of the H. signifer lineage into freshwater habitats appears to be relatively recent [47], it is not unexpected that H. signifer would experience higher salinity stress in freshwater than in brackish water.…”
Section: Discussionmentioning
confidence: 99%